Development of augmented reality learning media to improve mathematical problem-solving skills of 8th grade junior high school students - Al-jabar, Sheila Zalzabilla; Rosidah, Siti; Rosidah, Eka Ririn Nur (CV. Pustaka Literasi Ilmiah, 2024)
This research aims to develop learning media that can assist students in enhancing their mathematical problem-solving skills in 8th grade junior high school. This study utilizes a design research method with a development study approach conducted in two phases: initial design and formative evaluation, including self-evaluation, prototyping (expert review, one-to-one, and small groups), and field research conducted at SMP Negeri 7 Cimahi. The research subjects consist of 35 students from class VIII E of the junior high school. Data collection techniques used in this study include documentation, interviews, student response questionnaires, and tests. The research data are analyzed quantitatively and qualitatively. The data analysis results reveal that this study produces a logically reasoned mathematical thinking for Augmented Reality learning media on two-dimensional solid shapes that are valid, practical, and have potential effects. In this regard, the Augmented Reality learning media has valid and constructive content, as well as language validation from expert reviews. Conversely, the practicality of the Augmented Reality learning media has been achieved through revisions based on one-to-one feedback and small group discussions. Furthermore, the prototype of the Augmented Reality learning media has shown potential effects in enhancing students' mathematical problem-solving skills.